Effect of a four-decade long application of fertilizers, farmyard manure and lime, on forms of soil acidity and their relationship with yield of wheat and maize in an acid Alfisol. (3rd July 2018) - , Rajneesh; Sharma, R.P.; Sankhyan, N.K.; Kumar, Rameshwar; Sepehya, Swapana
ABSTRACT: The present investigation was undertaken in the on-going long-term fertilizer experiment initiated during 1972 at experimental farm of Department of Soil Science, Himachal Pradesh Agricultural University, Palampur, India. Continuous application of fertilizers either alone or in combination with farmyard manure (FYM)/lime affected different forms of soil acidity (total acidity, total potential acidity, pH dependent acidity, extractable acidity, exchangeable acidity, and non-exchangeable acidity) significantly, in surface and sub-surface layers. Continuous cropping with the application of lime and optimal doses of fertilizers decreased different forms of soil acidity at all the depths, significantly. Highest productivity of wheat and maize was recorded in 100% (nitrogen, phosphorus, potassium) NPK + FYM, which was at par with 100% NPK + lime. Different forms of soil acidity were found to be negatively correlated with wheat and maize yield. Grain and straw/stover yield of wheat and maize showed the highest negative correlation values with non-exchangeable acidity.